Ion-Pair Complex of Trimethoprim with Alizarin Yellow and its Determination and Extraction by LLE and DLLME - Araf I. Jabbar; Mohammed Z. Thani; Ali I. Khaleel (Tikrit Journal of Pure Science)
For the analysis of trimethoprim medication in its pure form and pharmaceutical formulations, precise and accurate microextraction techniques with UV-Vis measurement have been developed and confirmed. In this study, LLE and DLLME procedures were utilized for the separation, pre-concentration, and evaluation of trimethoprim in pure form and pharmaceutical preparations by UV-Vis spectroscopy at 390 nm. The method was validated and applied to the evaluation of trimethoprim in pharmaceutical formulations. Several experimental factors containing the type of dispersive and extraction solvents and their volumes, pH, temperature, and centrifuging time were carried out. Under the ideal conditions, the procedures were linear in the range of 2–45 and 1-10 mg/L, with a coefficient of determination (R2) of 0.9961 and 0.9992 for LLE and DLLME, respectively. The limit of detection (LOD) was 1.52 and 0.21 mg/L. Recovery of the target analyte in pharmaceutical formulations was 99.3%-104.9%.